Container shipping route design incorporating the costs of shipping, inland/feeder transport, inventory and CO2 emission. Issue 4 (December 2017) - Tran, Nguyen Khoi; Haasis, Hans-Dietrich; Buer, Tobias
Abstract As container shipping networks have become important components in global supply chains, route design should take both maritime and inland factors into consideration. In this article, a model is proposed to optimise container flows between two continents via an end-to-end service. The model is concerned not only with the design of an optimal shipping route but also with inland connections between hinterlands and ports. The objective is to minimise total costs, consisting of ship costs, port costs, inland/feeder transport costs, inventory costs and CO2 costs. The model is applied to the actual trade between Europe and the United States. Computational outcomes show that ship costs and port costs (port dues and terminal handling charges) represent less than one third of total costs. Therefore, themaritime network is only a part of a bigger system and piecemeal optimisation may not guarantee the optimisation of the whole network. Inland/feeder transport costs contribute the most to total costs, and they are influenced significantly by port choice. Although the use of a greater number of ports results in longer distances and higher shipping costs, this benefits in terms of lower distribution costs between hinterlands and ports. Inventory costs play a considerable part in total costs and they increase as vessel capacity goes up. In other words, these costs present a barrier to the introduction of bigger vessels. Optimal size is obviously a trade-offs between inventory and shipping costs.